Control Strategy of Thyristors Switched SVCs with High Power Quality - Dmitry Ivanovich Panfilov (Transactions on Environment and Electrical Engineering, 2018)
In this paper, new static VAR compensators SVCs schemes for inductive and capacitive reactive power are developed. The provided schemes improve the flexibility and power system quality of SVCs by developing new circuit topologies with new control strategy of the reactive power. New circuit schemes are introduced for thyristors switched reactors TSR and thyristors switched capacitors TSC to design harmonic-free SVC with higher discrete number of reactive power levels. This paper provides the control algorithm and block diagram of the new SVCs schemes. The switching strategies of TSR and TSC are described and implemented. The new scheme of TSC requires special modifications to decrease transient effects and implementation of specific switching strategies to acquire SVC with high power quality indexes.